A high energy, wavelength and repetition rate tunable eye-safe picosecond optical parametric oscillator. (15th February 2019) - Liu, Ke; He, Li-Jiao; Peng, Qin-Jun; Wang, Xiao-Jun; Bo, Yong; Liu, Zhao; Yang, Feng; Zong, Nan; Yuan, Lei; Yang, Jing; Cui, Da-Fu; Xu, Zu-Yan
Abstract: A wavelength and pulse repetition rate (PRR) tunable eye-safe picosecond (ps) optical parametric oscillator (OPO) with high energy is developed using a novel method that operates the OPO in a ps regenerative amplifier (RA). With this method, the PRR can be conveniently tuned and a compact kHz ps OPO can be achieved with a pulse energy of 1–3 orders of magnitude higher than previous works. Based on an angle phase matching type II ( θ = 41.4°, ϕ = 0°) KTA crystal, signal wavelength tunability from 1501 nm to 1565 nm is realized at the PRRs of 5 kHz and 10 kHz, respectively. The highest pulse energy of 21.6 µ J with a pulse width of about 6 ps is obtained at the PRR of 5 kHz and a wavelength of 1532 nm.